Razlike v prostorskih vzorcih mestnega turizma na Dunaju in v Pragi - Kádár, Bálint (Urbani izziv, 2013)
In Central Europe the two major urban tourism destinations are Vienna and Prague - with both registering the same number of foreign arrivals in 2011. Despite the two cities being similar in their size and range of cultural tourism, they differ significantly in tourists' spatial distribution and spaceusage. In Prague, congestion, overcrowding and the mono-functional use of the city centre is well known and documented, whereas in Vienna the city centre hosts a similar number of visitors without conflicts between local functions and tourism. Data obtained from geographically-referenced photography of the two cities uploaded to image-sharing web sites were used to build graphs of the spatial distribution of tourist attractions and routes. Analysing these comparable graphs resulted in some possible explanations regarding the differences in the two cities' tourist systems. These are mainlyrelated to the morphological layout of the two cities and their divergent approaches to developing urban tourism infrastructures over the pastdecade.
Keywords: Dunaj; geografija turizma; mesta; Praga; Prague; tourism; turizem; urbani prostor; urbanistični razvoj; Vienna